THE INVESTIGATION OF THE FON3 CATALOGUE DATA USING WIELEN METHOD - Akhmetov, V. S. (Одеські астрономічні публікації, 2016)
The method described by Wielen is very efficient provided the data under comparison are independent quantities. In this case, dispersion of position or magnitude differences is equal to the sum of their dispersions, because the index of correlation between the data is set zero. Using three or more independent catalogues, it is easy to estimate the external accuracy of each of them. For the cross-identification of objects, we have used the search window with a 0.5 arcsec radius. Final dispersions were calculated for every sub-range of magnitudes, for the stars with individual differences of position and magnitude exceeding three standard deviations being rejected. The following catalogues have been used for comparison with the FON3: XPM, PPMXL and UCAC4 in the Northern hemisphere. The dispersions of positions or magnitudes are calculated with the use of about 18 million common stars from these catalogues. The results presented in this work is consistent with analysis of the random errors of positions and magnitude that had been described by authors of FON3 catalog.